Causal Inference and Genome-Wide Perturb-Seq Reveals Tau as Downstream Biomarker but not Driver of Diseases - Huang, Zhiyuan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Tau is a protein created by alternative splicing of the gene MAPT, which plays an important role in stabilizing the internal structure of neurons. While Tau has been strongly associated with neurodegenerative diseases like Multiple Sclerosis (MS) and Alzheimer’s disease, it remains unclear whether Tau is the cause of these diseases or merely a downstream biomarker. To investigate the causal association between MS and Tau levels, a Mendelian randomization (MR) analysis was performed and the results indicated that MS can causally elevate blood Tau expression. Specifically, for every one log-odds increase in MS risk, blood MAPT expression increases by 0.063 standard deviations. However, the reverse MR analysis did not show any evidence suggesting that increased blood Tau levels doesn’t affect the risk of developing MS. To gain further insights into the regulatory mechanisms of Tau and its relationship with neurodegenerative disease, we utilized Perturb-seq, a single-cell sequencing method that enables the mapping of transcriptional effects resulting from genetic perturbations. Though analyzing the transcriptomic data from genome-wide knockouts in a human cell line, it turned out that MAPT knock-out has relatively small transcriptomic impact. We also identified that genes regulating Tau, but not genes regulated by Tau, are enriched with neurodegenerative disease-related pathways. These findings suggest that Tau may serve as a downstream biomarker rather than an initiator of neurodegenerative disease, implying that future gene-based interventions should focus primarily on the upstream regulators of Tau instead of targeting Tau itself.